1998
DOI: 10.1159/000017846
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Topical Antibiotics for Acne Treatment

Abstract: Topical use of antibiotics is currently a widely accepted effective and safe treatment for acne. A review of the articles published in the past 30 years revealed that topical application of antibiotics such as erythromycin, clindamycin or tetracycline showed clinical effectiveness for mild to moderate inflammatory acne, especially when they are combined with zinc, tretinoin or benzoyl peroxide, while they showed little influence on noninflammatory acne. The main mechanism of action of topical antibiotics for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 21 publications
0
33
0
2
Order By: Relevance
“…9,10 The adverse effects of topical antiacne agents include burning, erythema, scaling, flare-up, photosensitivity, and bacterial resistance. 4 Tretinoin (TRA) and BPO are used individually and in a cyclic manner for acne treatment.…”
mentioning
confidence: 99%
“…9,10 The adverse effects of topical antiacne agents include burning, erythema, scaling, flare-up, photosensitivity, and bacterial resistance. 4 Tretinoin (TRA) and BPO are used individually and in a cyclic manner for acne treatment.…”
mentioning
confidence: 99%
“…Having shown favorable clinical effects on acne in most clinical trials, antibiotics, above all erythromycin, clindamycin and tetracyclines, have become an integral part of both topical and systemic acne therapy [1]. As discussed above, propionibacteria have increasingly developed resistances to these antibiotics in recent decades, especially to erythromycin and clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…This role appears to relate essentially to the conversion of microcomedones into the inflammatory efflorescences of acne. This hypothesis is strongly supported by the fact that most studies have shown that antibiotics reduce mainly the inflammatory efflorescences of acne, while only a few studies have also suggested an effect on comedone counts [1]. Morphologically and immunohistochemically, the inflammatory reaction consists of an accumulation of CD4+ T cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…Antimikro bielle Wirkungen betreffen die Suppressi on des Wachstums von P. acnes [27], nicht antimikrobielle, meist antiinflammato rische Wirkmechanismen betreffen die Hemmung der Lipaseproduktion durch P. acnes [28], die Hemmung der Leuko zytenchemotaxis [26] und die Neutralisa tion von Hydroxylradikalen [22].…”
Section: Wirkmechanismenunclassified